Bifacial stamping for high efficiency perovskite solar cells. Issue 1 (30th November 2018) - Zhang, Yong; Kim, Seul-Gi; Lee, Donghwa; Shin, Hyunjung; Park, Nam-Gyu
Abstract : We report a novel approach for a fast phase transition of FAPbI3 at low-temperature and the effective removal of interfacial recombination in MAPbI3 . Abstract : We report a novel approach for a fast phase transition of FAPbI3 (FA = formamidinium) at low-temperature and the effective removal of interfacial recombination in MAPbI3 (MA = methylammonium). This method also allows for printing (patterning) of the perovskite on a desired area. The pre-annealed MAPbI3 and δ-phase FAPbI3 films were prepared by spin-coating DMSO and a polar aprotic solvent admixed precursor solution at 65 °C and 100 °C for about 1 min, respectively, to form adduct films containing DMSO. Two films were sandwiched without pressure by a method called bifacial stamping, and annealed at 100 °C for 9 min, which resulted in complete δ → α phase transition of FAPbI3 and led to a power conversion efficiency (PCE) of 18.34%. The stamped MAPbI3 demonstrated a PCE of 20.18% that was much higher than the conventionally annealed MAPbI3 (∼17.4%) mainly due to a much higher fill factor and open-circuit voltage. Optical and structural studies revealed that DMSO-mediated ion exchange plays a vital role in the phase transition of FAPbI3 and the surface modification of MAPbI3 . Theoretical calculation results further support the role of DMSO in the phase transition at low temperature. Stamping was applied to EAPbI3 (EA = ethylammonium), where photoinactive yellow EAPbI3 changed to photoactive EAPbI3 with a PCE of 13.02% after stamping with MAPbI3 . The DMSO-mediated EA/MA ion exchange reaction during the stamping process created a new layer having a gradient solid solution of EAPbI3 and MAPbI3, which was responsible for the abnormally high PCE of the EAPbI3 based perovskite solar cell. Facilitated ion transport by a Lewis base (such as DMSO) reservoir in the perovskite adduct film is suggested to be involved in the bifacial stamping procedure.